2021
DOI: 10.1101/2021.05.13.444058
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Light at the end of the tunnel: FRAP assay reveals that plant vacuoles start as a tubular network

Abstract: Plant vacuoles play key roles in cellular homeostasis performing catabolic and storage functions, regulating pH and ion balance 1,2. The essential role of vacuoles for plant cell viability makes them a notoriously difficult subject to study. As a consequence, there is still no consensus on the mechanism of vacuolar establishment and the source of membrane material for it. Our previous suggestion of endoplasmic reticulum (ER) being the main contributor of membrane for growing young vacuoles3 was recently challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Together with the partial ER-localization of NET4 and its ability to interact with the ER-PM contact site protein VAP27 (Wang et al, 2014), this establishes a direct connection between the ER and the vacuole. This could represent an efficient way to provide ER-derived lipids to the expanding vacuole or to deliver distinct sets of proteins to developing (pro-) vacuoles (Viotti et al, 2013; Minina et al, 2021). NET3- and NET4-mediated bridging of the ER and the vacuole to establish a membrane contact site would be novel in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the partial ER-localization of NET4 and its ability to interact with the ER-PM contact site protein VAP27 (Wang et al, 2014), this establishes a direct connection between the ER and the vacuole. This could represent an efficient way to provide ER-derived lipids to the expanding vacuole or to deliver distinct sets of proteins to developing (pro-) vacuoles (Viotti et al, 2013; Minina et al, 2021). NET3- and NET4-mediated bridging of the ER and the vacuole to establish a membrane contact site would be novel in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The classic model as demonstrated by 2D‐TEM indicates that vacuoles stem from Golgi and post‐Golgi‐derived vesicles, which fuse with each other to form the central vacuole (Marty, 1999). Research using 3D confocal imaging of living cells with 200‐nm resolution together with fluorescence recovery after photobleaching (FRAP) assay indicated that vacuoles originated from tubular network (Minina et al ., 2021). Immunogold‐TEM of high‐pressure frozen/freeze‐substituted, and serial block‐face scanning electron microscope (SBF‐SEM) of chemically fixed samples have revealed a single interconnected vacuole inside the cell which originates from the ER, together with connection of ER‐vacuole and ER‐to‐vacuole transfer (Viotti et al ., 2013; Kolb et al ., 2015; Lofke et al ., 2015; Scheuring et al ., 2016).…”
Section: Vacuole Biogenesis and Vacuolar‐trafficking Pathways In Plantsmentioning
confidence: 99%